(untitled) (Research, Society and Development, 2021)
The training process of a teacher requires different experiences and experiences, with the students’ dialogue and context as basic elements for the construction of new knowledge. It is in this path of debates, provocations and discussions that this article is constituted, signaling paths, possibilities and epistemes in the educational context of teachers, with a view to contributing to the process of social (trans)formation of students. Considering these concerns, this article aims to analyze the training of teachers, paying attention to the diversity of knowledge, experiences and experiences present in the educational environment and that make up the knowledge of teachers. In terms of methodological aspects, it can be said that the present study presents a qualitative approach, focusing on a bibliographical research, whose data analysis took place through Discursive Textual Analysis, with the creation of emerging categories. It can be said that teacher education needs to insert the students’ reality into the teaching and learning dynamics, signaling paths for human, critical and emancipatory education, paying attention to the plurality of knowledge, experiences and identities that are present in the sociocultural environment. Likewise, permanent teacher training is essential, with a view to contributing to debates involving science, culture, politics, economy, environment and society, discussing hegemonic ideas and positions that end up alienating subjects.